The youth's interpersonal communication with friends and family: The impacts of social media - Maharsi Widya Astuti; Riny Jefri; Lely Novia (Center for Humanities and Innovation Studies, 2023)
This study aims to determine whether or not the use of social media by youth reduces their interaction with family. For the sample in this study, a simple random sampling method was used as part of a quantitative method. Students from the Business English Communication classes in the 2019–2020 and 2021 batches served as the study's subjects. In this study, there are two variables: social media (X) and interaction with family (Y). Two different types of questionnaires, open-ended and closed-ended, were used as the instruments and data collection techniques. The normality test, linearity test, and t-test for hypothesis testing were used in this study for data analysis. Data analysis was done based on the questionnaire results, and the outcomes for the two variables fell into the high category. The results of the study show that social media reduces adolescents' social interaction with family. The t-test results demonstrated that H0 is rejected when the value of t-count exceeds t-table (11.385> 2.002). Therefore, it can be concluded that the results support the Alternative hypothesis, which states that youth use of social media reduces the social interaction with family.